Social class as a moving average - Malcolm Brynin (University of Essex, Institute for Social and Economic Research (ISER), 2010)
Are social (occupational) classes coherent, distinct entities? While they reflect an underlying reality, they are more fragmented than theory suggests. It is hypothesised that skill mismatches mean that each class includes a substantial proportion of poorly paid people who could be in the class below and highly paid people who could be in the class above, or in a class alone. This is tested for the service classes using the British Labour Force Survey. It is then shown using the British Household Panel Study that people within the service classes have differing class backgrounds, different class perceptions, and different political views depending on their hourly pay.
Keywords: 330; Social class; Wages; Skills; Sozialstruktur; Soziale Schicht; Einkommen; Großbritannien